ChemInform Abstract: Sequential Growth at the Sub‐10 Nm Scale of Cyanide Bridged Coordination Networks on Inorganic Surfaces. Issue 3 (21st January 2014) - Tricard, Simon; Fabrice Charra, Fabrice Charra; Mallah, Talal
Abstract Review: 41 refs.